2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6854474
|View full text |Cite
|
Sign up to set email alerts
|

Temporal synchronization of multiple audio signals

Abstract: Given the proliferation of consumer media recording devices, events often give rise to a large number of recordings. These recordings are taken from different spatial positions and do not have reliable timestamp information. In this paper, we present two robust graph-based approaches for synchronizing multiple audio signals. The graphs are constructed atop the over-determined system resulting from pairwise signal comparison using cross-correlation of audio features. The first approach uses a Minimum Spanning T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Kammerl et al [12] presented two graph-based approaches able to synchronize several audio signals. Features like Spectral Flatness or Zero-crossing Rate are extracted from the audio sources.…”
Section: Related Workmentioning
confidence: 99%
“…Kammerl et al [12] presented two graph-based approaches able to synchronize several audio signals. Features like Spectral Flatness or Zero-crossing Rate are extracted from the audio sources.…”
Section: Related Workmentioning
confidence: 99%
“…Given a collection of User Generated audio or video Recordings (UGRs), several approaches have been proposed about how to exploit the available visual and audio content in order to identify video clips associated to the same moment of a public event, to estimate the overlap between these clips and to synchronize them along the same temporal axis. The audio content is a key to solving this problem and several works have shown that the temporal relations between different UGRs can be revealed by exploiting the correlations in their associated audio streams [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…An emerging research challenge is to investigate different means by which this low-quality but organized content can be synergistically processed and combined, so as to improve both audio and visual aspects of the captured public event (see references in [6] for applications related to visual content). This potential is examined in this paper from the perspective of…”
Section: Introductionmentioning
confidence: 99%